Study of the Relationship between Tourism Industry and Improving the Quality of Life of the Host Society (Case Study: Sarein City) - Mehdi karoubi; yavar babaei; Narges Sheikhhasani; mohammadali Aghande (توسعه اجتماعی)
Tourism industry has different effects on the destination. These effects can be social, economic, cultural and environmental. Based on a sustainable development model, these effects should reflect the quality of life of the host community and improve the quality of life of the tourist destination. The purpose of this study was to investigate the effect of tourism industry on improving the quality of life of host society in Sarein city. This research is a descriptive-survey research based on a questionnaire. The statistical population is the residents of Sarein city. The sample size is 360 people based on the Cochran formula, which is selected by available sampling method. Data analysis and hypothesis testing were performed by using confirmatory factor analysis and structural equation modeling using SPSS and SMARTPLS software. The results of the research showed that from the viewpoint of the host society, the economic effects of tourism with a 0.427 coefficient have a positive and significant positive effect on social well-being on the material well-being and social-cultural effects of tourism with a coefficient of 0.321. Also, the variables of economic effects, material well-being and social welfare with a coefficient of 0.175, 0.345 and 0.385 have a positive and significant effect on quality of life, but socio-cultural effects on the quality of life of the host society have no significant effect. Finally, the results of the study showed that, in total, independent variables, 55.8% of the changes in the dependent variable (quality of life) are explained.